Conflicts over natural resources in the Global South : conceptual approaches - Bavinck, Maarten; Mostert, Erik (CRC Press, 2014)
Inhabitants of poor, rural areas in the Global South heavily depend on natural resources in their immediate vicinity. Conflicts over and exploitation of these resources - whether it is water, fish, wood fuel, minerals, or land - severely affect their livelihoods. The contributors to this volume leave behind the polarised debate, previously surrounding the relationship between natural resources and conflict, preferring a more nuanced approach that allows for multiple causes at various levels. The contributions cover a wide array of resources, geographical contexts (Africa, Asia and Latin Ame.
Keywords: Natural resources.; Environmental policy.; elektronické knihy; electronic books